2018
DOI: 10.3174/ajnr.a5728
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Synthetic MR Imaging Sequence for Spine Imaging

Abstract: Our study shows that synthetic MR imaging is feasible in spine imaging and produces, in general, good image quality and diagnostic confidence. Furthermore, the non-negligible time savings and the ability to obtain quantitative measurements as well as to generate several contrasts with a single acquisition should promise a bright future for synthetic MR imaging in clinical routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…The results were different from those reported by Vargas et al. ; they reported lower SNRs in the dorsolumbar region for synthetic MRI than for conventional sequences (24). The SNR can be drastically altered by multiple MR parameters, such as field of view, slice thickness, field strength (28), and so on.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results were different from those reported by Vargas et al. ; they reported lower SNRs in the dorsolumbar region for synthetic MRI than for conventional sequences (24). The SNR can be drastically altered by multiple MR parameters, such as field of view, slice thickness, field strength (28), and so on.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, some studies that applied synthetic MRI to the knee have reported good diagnostic ability, which was generally accepted by radiologists and clinical doctors (1923). A study reported that synthetic MRI had a lower signal-to-noise ratio (SNR) in the lumbar region than did conventional MRI (24). However, the study was performed using a 1.5-T MR scanner.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, the optimization of the spinal synthetic MRI (SyMRI) is highly recommended. SyMRI is a technique based on a quantitative approach, that allows the quantification of absolute-tissue physical properties by the acquisition of a single sequence obtaining images with different weighted (T1, T2, STIR, PD, PSIR); this means a potentially significant reduction of the acquisition time with the aim, still under investigation, to not reduce the diagnostic accuracy [ 24 , 25 ].…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…64 Feasibility studies comparing synthetic and conventionally acquired 2D sequences of the spine showed good interobserver agreement, although with greater artifacts. 65,66 To date, synthetic CT data obtained from MRI have not been used successfully with neuronavigational software and are still under investigation. 67 Thorough evaluation of synthetic MRI in spine applications may yield further time savings and expanded applications for both 2D and 3D protocols.…”
Section: Further Directionsmentioning
confidence: 99%